Emancipation and Opportunity: Position of Slaves in Islam and the Islamicate World with a Special Reference to Delhi Sultanate, circa 1206-1290 AD - Chowdhary, Mir Kamruzzaman (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2024)
This paper explores how slaves were treated in Islam, particularly within the larger Sunni vision of shari’a. In fact, this paper argues that slavery provided an opportunity for people from the lower strata of society to gain a position of power. In this regard, the paper takes the early Delhi Sultans (c.1206-c.1290) as a template to explain how slavery acted as a tool of emancipation and opportunity within the Islamicate[1] world during the medieval period. Unlike western societies, why slaves (Mamluks) would enjoy such an overwhelming power and authority in the Islamicate world requires adequate scholarly attention. Who were the people primarily recruited as enslaved people? What were the reasons for their recruitment? This paper searches answer for these questions. The paper also endeavours to understand the differences between slavery and the mamluk system that developed in the Islamicate world in the ninth century. How did slaves become the king? Did the Turks, who were predominantly enrolled as mamluks reciprocate the process of the ghulam system started by the Abbasid Caliph? If so, what was the reason for a person to choose slavery over free life? This paper examines all these questions to understand whether it was the Islamic ethical teaching that emancipated slaves or it was the political need of that age that converted slavery, particularly the mamluksystem, into an opportunity for many.[1] Islamicate would refer not directly to the religion, Islam, itself, but to the social and cultural complex historically associated with Islam and the Muslims, both among Muslims themselves and even when found among non-Muslims. Massimo Campanini, “Heidegger in the Islamicate World,” in Rivista di Filosofia Neo-Scolastica, Vol. 111, No. 3 (2019), pp. 735-740.